Media Sosial: Informasi dalam Jerat Ekonomi Politik - mustofa mustofa mustofa (iLearning Journal Center, 2020)
Social media has always been a part of most people's activities. This is mainly because there are many positive benefits behind the presence of social media. However, these positive benefits save the political economy trap that social media users are not aware of. This research wants to elaborate the political economy meshes hidden behind social media where the user's personal data information can be converted into commodities. Using a descriptive-qualitative approach, the method used in this study is the library research method. Data collection techniques are carried out by tracing the literature related to the problem in this study both in the form of books and journal articles. The results of this study indicate that the personal data information of social media users has the potential to be converted into commodities both by the service providers and by certain other parties for economic purposes. Information that has been converted into commodities can be sold to agents of various products in the real world or used for campaign wins.